Mirizzi syndrome-differential diagnosis with cholangiocarcinoma: case report - Adame, Jorge D. E.; Anguiano, Tania I. D.; Cortes, David S.; Trejo , Sandra L. (International Journal of Research in Medical Sciences, 2023)
Mirizzi syndrome is a rare complication of gallstone disease and poses a diagnostic challenge for general surgeons due to its clinical presentation, which resembles other pathological entities such as cholangiocarcinoma. We present a clinical case of a 68-year-old female patient with symptoms of jaundice and right upper quadrant pain. During the patient's diagnostic workup, altered liver function tests were documented, highlighting obstructive pattern hyperbilirubinemia, elevated tumor marker CA 19.9, and suspicion of biliary tract tumor based on imaging studies. However, surgical and pathological confirmation revealed Mirizzi syndrome. This case emphasizes the importance of considering differential diagnoses in patients presenting with obstructive jaundice to provide timely and appropriate treatment.